Signaling–chemokine axis network in brain as a sanctuary site for metastasis. Issue 4 (6th September 2018) - Azizidoost, Shirin; Asnafi, Ali Amin; Saki, Najmaldin
Abstract: Background: Brain metastasis remains a major cause of death in patients with solid cancers. The co‐operation between several molecular factors such as chemokines, chemokine receptors, and signaling pathways is involved in the pathogenesis of brain metastasis mostly from solid tumors. In this review, we examine the possible role of chemokine/receptor axis, as well as signaling pathways as prognostic biomarkers in brain metastasis. Methods: Relevant English language literature were searched and retrieved from Google Scholar search engine (1993–2017). The following keywords were used: "chemokine, " "signaling pathway, " "brain, " "metastasis, " and "niche." Results: Increased expression of chemokines like CXCL12 and dysregulated signaling intermediates such as Notch in patients with solid tumors (e.g., breast cancer) is associated with brain metastasis. Conclusions: As biomarkers for brain metastasis, chemokine, and signaling intermediates are potential prognostic factors in a number of solid tumor, including breast cancer, melanoma, and lung cancer. Abstract : 1. Chemokines secreted from cancer cells are involved in angiogenesis and vascularization in brain metastasis. 2. Targeting a chemokine receptor could be a strategy to inhibit metastasis from solid tumors. 3. Signaling could cooperate with the chemokine network to induce metastasis.